1995
DOI: 10.1103/physrevlett.74.4354
|View full text |Cite
|
Sign up to set email alerts
|

Saito and Oshiyama Reply:

Abstract: 1] on our Letter [2], Watkins shows his confidence that large pairing distortion (LPD) takes place instead of the resonant-bond distortion (RBD) in the divacancy (U2) for both V2+ and V2 . His assertion is based on the EPR measurement beautifully carried out by Watkins and Corbett in the 1960s [3]: They have established that the pairing distortion is consistent with the EPR spectra under uniaxial stress. We still argue, however, that the RBD occurs for V2 and the small pairing distortion occurs for V&+, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
140
1
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(148 citation statements)
references
References 3 publications
4
140
1
3
Order By: Relevance
“…Also, Seong and Lewis found a RB configuration as the ground state structure for V 0 2 [5]. Although these calculations can explain the wave function character of the highest occupied state, the sense of the distortion is in disagreement with the experimental finding of rebonding by pairs [6,7]. In addition, the calculated energy difference between the RB configuration and the pairing configuration for V 2 2 was only 2.4 meV, much too small for a definite conclusion.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Also, Seong and Lewis found a RB configuration as the ground state structure for V 0 2 [5]. Although these calculations can explain the wave function character of the highest occupied state, the sense of the distortion is in disagreement with the experimental finding of rebonding by pairs [6,7]. In addition, the calculated energy difference between the RB configuration and the pairing configuration for V 2 2 was only 2.4 meV, much too small for a definite conclusion.…”
mentioning
confidence: 71%
“…In contrast with these experimental findings, theoretical calculations so far [2][3][4][5][6][7][8], which have mainly employed the ab initio plane-wave supercell technique with 64 atoms, have found a different JT distortion both in terms of the magnitude and the sense of the relaxation. For V 2 2 , Saito and Oshiyama found the atomic displacements opposite to the experimental finding [4] resulting in d 12 .…”
mentioning
confidence: 80%
“…In Ref. [5] it was shown that the difference between the radius of a neutron and a proton would grow with density and it was then claimed that this would lead to a violation of the Behrends-Sirlin-Ademollo-Gatto [6,7] (BSAG) theorem. This result, which was a consequence of an incorrect application of the constraint equations in the bag model, is wrong.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Also, the ab initio calculations by Seong and Lewis 5 give a resonant bond structure for V 2 0 (d 13 ϭd 23 Ͻd 12 : a u 2 ). These calculations are based on the density-functional theory ͑DFT͒ in the local-density ͑LD͒ approximation.…”
mentioning
confidence: 99%